1968
DOI: 10.1037/h0026057
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and successive contrast effects in human-probability learning.

Abstract: 2 experiments investigating concurrent simultaneous and successive contrast effects with human 5s in a probability learning task are reported. Successive and simultaneous negative contrast effects were noted with 2 nonzero levels of incentives. These effects were not obtained with a paired zero and nonzero incentive level. An absolute magnitude hypothesis for the latter condition was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

1969
1969
1975
1975

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…The same test also revealed significant differences (p< .01) between Groups 12-15 and 12-30 and Groups 1-15 and 1-30, the direction of the differences being in favor of the 15-see delay groups. This finding suggests the occurrence of a "new" negative eontrast effect where positive contrast was expected, a finding recently reported in human studies involving a two-choiee probability task (Halpern et al, 1968). DISCUSSION The results of Phase 1 are c1ear in showing that speed is an additive function of magnitude and delay of reward.…”
Section: Procedures Preliminary Trainingsupporting
confidence: 68%
“…The same test also revealed significant differences (p< .01) between Groups 12-15 and 12-30 and Groups 1-15 and 1-30, the direction of the differences being in favor of the 15-see delay groups. This finding suggests the occurrence of a "new" negative eontrast effect where positive contrast was expected, a finding recently reported in human studies involving a two-choiee probability task (Halpern et al, 1968). DISCUSSION The results of Phase 1 are c1ear in showing that speed is an additive function of magnitude and delay of reward.…”
Section: Procedures Preliminary Trainingsupporting
confidence: 68%
“…Negative but not positive contrast was also demonstrated when the payoff 5 received for a correct prediction was varied randomly on each trial (Halpern et al, 1968;Lipkin, 1968;Schnorr et al, 1966). For this within-5 manipulation of incentive, one of two incentive magnitudes was stamped on the back of each card in a shuffled deck (e.g., l£ or Sji), and when predicting which of two stimulus alternatives was on the face of a given card, 5s "risked" the incentive magnitude indicated on the back.…”
Section: Virginia Polytechnic Institute and State Universitymentioning
confidence: 91%
“…In the successive manipulation of incentive 5s are given initially one level of incentive for several prediction trials and subsequently shifted to a higher or lower level. Those PL studies that incorporated this successive manipulation of incentive observed negative but not positive contrast (Halpern et al, 1968;Swensson, 1965). That is, after 5s received a shift from a high to a low level of incentive, their prediction proportions for the more frequently occurring stimulus were lower than those of control 5s who received the same low incentive magnitude throughout the experimental session.…”
Section: Virginia Polytechnic Institute and State Universitymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the frequency with which the stimulus events are guessed, a NCE but no PCE; neither a NCE nor a PCE; and both a PCE and a NCE have all been reported (cf. Chapman and Halpern, 1969;Halpern, Schwartz, & Chapman, 1968 The present experiments sought to clarify an.j to extend the research on contrast effects with hLman subjects by using a procedure which was more nearly analogous to the simple conditionjng experiments with animals than the procedures with human subjects which had been previously employed. Thus, not only was the experimental task designed to resemble the instrumental running response of the rat in the "straightaway," but in the same way that magnitude of the reward which the rat receives in the goal box is typically not dependent upon the "quality" or "speed" of its' performance, no such contingency held in the present procedure.…”
mentioning
confidence: 99%